Peran Guru dan Orang Tua pada Anak Berdiagnosa ADHD di Sekolah Dasar Negeri Gondrong 4 - Septy Nurfadhillah; Siti Nurfaizah; Hilwatunnisa Nurlayali; Putri Andini (Lembaga Yasin AlSys, 2022)
Attention Deficit/Hyperactivity Disorder ADHD is a child who has a disorder that attacks children and makes it difficult for the sufferer to focus on one thing at a time. The role of parents and teachers is needed for children with special needs and is a supporting factor for the success of children with special needs in inclusive education. The involvement of parents in education is a driving and determining factor in the development of inclusive education. This study aims to determine the role of teachers and parents in children diagnosed with ADHD at SDN GONDRONG 4. This research method uses descriptive qualitative methods so that the data exposure is easy to understand. The selection of research subjects consisted of one classroom teacher, one GPK teacher, (special assistant teacher), and one student diagnosed with ADHD. The results of the study indicate that there are students with special needs who are categorized as ADHD. Students who have ADHD have difficulties during the direct learning process such as difficulty concentrating and recognizing letters.